Peer review: what are the OBJN responsabilities? - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
As other scientific journals, the Online braz j of nurs is a vehicle to exchange knowledge and scientific information within the scientific and professional community. But this task can be accomplished only after the peer-review select the papers and improve their qualities.